2016
DOI: 10.3389/fpsyg.2016.01763
|View full text |Cite
|
Sign up to set email alerts
|

Being in a Romantic Relationship Is Associated with Reduced Gray Matter Density in Striatum and Increased Subjective Happiness

Abstract: Romantic relationship, a widespread feature of human society, is one of the most influential factors in daily life. Although stimuli related to romantic love or being in a romantic relationship commonly result in enhancement of activation or functional connectivity of the reward system, including the striatum, the structure underlying romantic relationship-related regions remain unclear. Because individual experiences can alter gray matter within the adult human brain, we hypothesized that romantic relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 82 publications
1
14
0
4
Order By: Relevance
“…Selecting a long-term romantic partner is a key life decision and influences most aspects of our lives. Mate choice is associated with physical well-being, mental health, economic decision-making, workplace behavior, social interactions (see Diener & Seligman, 2002; Hill & Buss, 2006), and brain structure (Kawamichi et al, 2016). Previous research has identified some well-established sex differences in men’s and women’s mate preferences (Buss, 1989; Buss & Schmitt, 1993; Schmitt, 2005).…”
mentioning
confidence: 99%
“…Selecting a long-term romantic partner is a key life decision and influences most aspects of our lives. Mate choice is associated with physical well-being, mental health, economic decision-making, workplace behavior, social interactions (see Diener & Seligman, 2002; Hill & Buss, 2006), and brain structure (Kawamichi et al, 2016). Previous research has identified some well-established sex differences in men’s and women’s mate preferences (Buss, 1989; Buss & Schmitt, 1993; Schmitt, 2005).…”
mentioning
confidence: 99%
“…Although most of these brain imaging studies have reported that enlargement of the involved brain regions results from their intense and repeated activation, successful chess players, who required the realistic view (to maintain practical and efficient judgment without being influenced by emotional fluctuation; Hernández Hernández and Rodríguez-Mateo, 2006), consistently exhibited lower GMV in the striatum (Duan et al, 2012; Hänggi et al, 2014). Similarly, in terms of striatal modulation by social human relationships (Engelmann and Hein, 2013), our recent study also showed that being in a romantic relationship was associated with significantly lower GMV in the right dorsal striatum and increased subjective happiness (Kawamichi et al, 2016). Therefore, we suggest that the current findings that the Nurses showed lower GMV in the right striatum negatively correlated with the realistic view, might be a representation of morphological modulation due to their professional circumstances and experiences.…”
Section: Discussionmentioning
confidence: 54%
“…Además, aunque algunas participantes señalaron no tener la necesidad de tener pareja para sentirse bien consigo mismas, sí refirieron que había presión por parte del entorno cuando no tenían una relación de pareja. De acuerdo con Rodríguez-Castro et al (2015), las prescripciones sociales respecto a qué se entiende por amor podría derivar en una pérdida de la identidad propia, que se encuentra en la idealización del concepto "nosotros" en el ámbito de la pareja (Kawamichi et al, 2016;Valle y De la Villa, 2018). También se hallaron respuestas asociadas al mito "donde hay amor, hay sufrimiento", lo que implica la asunción y aceptación del malestar en la construcción de una relación afectiva, con mayor riesgo para las mujeres educadas en ser para otros (Bonilla y Rivas, 2018b).…”
Section: Discussionunclassified
“…Estos proceden del imaginario social acerca de la idealización del amor y representan una serie de creencias socialmente compartidas con implicaciones diferenciadas para hombres y mujeres (Bonilla y Rivas, 2018). La idealización de la relación romántica provoca que el concepto "tú/yo" pase a denominarse "nosotros", lo que puede desarrollar dependencia emocional bajo la necesidad de encontrar esa prescripción social dentro de la pareja (Kawamichi et al, 2016;Valle y De la Villa, 2018). Además, los imperativos sociales en las relaciones de pareja heterosexuales podrían impedir a las mujeres ser ellas mismas, ya que perderían la propia identidad con el objetivo de obtener el afecto del hombre (Rodríguez-Castro, Lameiras-Fernández, y Carrera, 2015).…”
unclassified